2015
DOI: 10.1590/0102-311x00075314
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da hanseníase no Tocantins, um estado hiperendêmico do Norte do Brasil, 2001-2012

Abstract: A hanseníase é hiperendêmica no Estado do Tocantins, Brasil. O objetivo do estudo foi analisar as tendências dos indicadores da hanseníase no Tocantins em 2001-2012. Análise de dados advindos do Sistema de Informação de Agravos de Notificação (SINAN). Incluíram-se casos novos de residentes no Tocantins. Calcularam-se os indicadores da hanseníase e analisaram-se as tendências temporais por meio de regressão polinomial. Houve tendência significativa e decrescente para a detecção geral (R2 = 0,40; p < 0,05) e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
77

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 17 publications
6
31
1
77
Order By: Relevance
“…The reality described converges with other published studies [18][19][20][21] By affecting mainly cutaneous cells and peripheral nerves, leprosy has high incapacitating potential, making it the object of research and social concern. The most aggressive forms of the disease, borderline and lepromatous, are grouped in multibacillary classification, established as those cases where the individual presents more than five skin lesions or with positive bacilloscopy (in this case, regardless of the number of injuries) [22] Multibacillary patients are responsible for the transmission of the disease, and are about 4 (four) times more likely to develop into physical disability [23].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The reality described converges with other published studies [18][19][20][21] By affecting mainly cutaneous cells and peripheral nerves, leprosy has high incapacitating potential, making it the object of research and social concern. The most aggressive forms of the disease, borderline and lepromatous, are grouped in multibacillary classification, established as those cases where the individual presents more than five skin lesions or with positive bacilloscopy (in this case, regardless of the number of injuries) [22] Multibacillary patients are responsible for the transmission of the disease, and are about 4 (four) times more likely to develop into physical disability [23].…”
Section: Discussionsupporting
confidence: 84%
“…On data reliability, few studies have proposed to study the SINAN for leprosy, but those which did it found flaws similar to those presented in this study, showing them in the assessment of the disability degree [19,[24][25]. The fragility of the information system can be related to the filling performed by professionals, the data processing, its inadequate typing or even neglect and lack of variables filling [19], but this is not the study object of analysis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A região Norte do Brasil é considerada zona endêmica de doenças infectocontagiosas, como hanseníase, síndrome da imunodeficiência humana adquirida (AIDS), leishmaniose, malária, leptospirose, tuberculose e hepatite 7,8,9,10,11,12,13,14 . E, ainda, configura local de doenças reemergentes como cólera e febre tifoide 12,15 .…”
Section: Introductionunclassified
“…The magnitude and trend of leprosy described in the study period indicate that, in isolation, the municipalization of control measures, with full coverage for diagnosis and treatment by primary care is not enough to achieve the elimination goal. [15].…”
Section: Discussionmentioning
confidence: 99%